Endoscopic submucosal dissection for colorectal dysplasia in inflammatory bowel disease: a US multicenter study - Ngamruengphong, Saowanee; Aihara, Hiroyuki; Friedland, Shai; Nishimura, Makoto; Faleck, David; Benias, Petros; Yang, Dennis; Draganov, Peter V.; Kumta, Nikhil A.; Borman, Zachary A.; Dixon, Rebekah E.; Marion, James F.; DʼSouza, Lionel S.; Tomizawa, Yutaka; Jit, Simran; Mohapatra, Sonmoon; Charabaty, Aline; Parian, Alyssa; Lazarev, Mark; Figueroa, Esteban J.; Hanada, Yuri; Wang, Andrew Y.; Wong Kee Song, Louis M. (Endoscopy International Open, 2022)
Background and study aims In patients with inflammatory bowel disease (IBD), endoscopically visible lesions with distinct borders can be considered for endoscopic resection. The role of endoscopic submucosal dissection (ESD) for these lesions is not well defined because of a paucity of data. We aimed to evaluate the outcomes of colorectal ESD of dysplastic lesions in patients with IBD across centers in the United States.Patients and methods This was a retrospective analysis of consecutive patients with IBD who were referred for ESD of dysplastic colorectal lesions at nine centers. The primary endpoints were the rates of en bloc resection and complete (R0) resection. The secondary endpoints were the rates of adverse events and lesion recurrence.Results A total of 45 dysplastic lesions (median size 30mm, interquartile range [IQR] 23 to 42 mm) in 41 patients were included. Submucosal fibrosis was observed in 73 %. En bloc resection was achieved in 43 of 45 lesions (96 %) and R0 resection in 34 of 45 lesions (76 %). Intraprocedural perforation occurred in one patient (2.4 %) and was treated successfully with clip placement. Delayed bleeding occurred in four patients (9.8 %). No severe intraprocedural bleeding or delayed perforation occurred. During a median follow-up of 18 months (IQR 13 to 37 months), local recurrence occurred in one case (2.6 %). Metachronous lesions were identified in 11 patients (31 %).Conclusions ESD, when performed by experts, is safe and effective for large, dysplastic colorectal lesions in patients with IBD. Despite the high prevalence of submucosal fibrosis, en bloc resection was achieved in nearly all patients with IBD undergoing ESD. Careful endoscopic surveillance is necessary to monitor for local recurrence and metachronous lesions after ESD.